Effect of Cold Front‐Induced Waves Along Wetlands Boundaries. Issue 12 (30th November 2020) - Kim, Jin‐Young; Kaihatu, James; Chang, Kuang‐An; Sun, Shih‐Heng; Huff, Thomas P.; Feagin, Rusty A.
Abstract: Along wetland shorelines, the energetic wave environment generated by cold fronts occurs more frequently than for major storms, yet their impact on wetland evolution processes has not been fully identified. To capture the changes in wave climate during the passage of cold fronts, a wave gauge was installed near a salt marsh edge in Galveston Bay, Texas, USA. A coupled wave‐hydrodynamic model, validated with the data, was used to assess the dominant processes of cold front induced surge and waves. During the measurement period, wind gusts and abrupt direction shifts during cold fronts produced high‐energy wave events that propagated toward the wetland edge. Before a cold front passed our study area, there was an initial increase in the water level inside the bay. As soon as the cold front passed and the wind direction shifted, large waves were created by strong winds. Over the first few hours, the relatively high water level reduced the depth limitations on these waves, allowing them to be quite large. However, as the waves struck the wetland edge at these higher water levels, vegetation intercepted and dampened the erosive force. Over the next few days, the water level dropped well below the mean tide, allowing plunging waves to impinge directly on the edge with a high‐energy flux. From the calculated wave power during the entire measurement period, it was found that cold front‐induced waves, despite their brief duration, had a high erosive impact on the evolution of the wetland edge. Plain Language Summary: Wetlands around the world have been significantly eroded due to climate changes and human‐induced local environmental changes. One of the causes of erosion is wind‐driven waves impacting the wetland boundary. The passage of cold fronts over confined bays creates energetic waves and increases the water level, exacerbating the impact of these waves on wetlands despite the relatively short duration. These events are far more frequent than hurricanes, and thus have a likely higher impact on wetlands processes. To capture the changes in wave climates during the passing of cold fronts, a wave gauge was installed near the Galveston Island wetland boundary during December 2015. A series of computer models were used to reproduce the tide and wave conditions, and determine which processes were dominant during fronts. Passing fronts generated waves and increased the water level at the wetlands. The approaching waves impacted the edge of wetlands for most of the time period; at times, however, the wetlands were inundated by the increased water level and the wave impact was lessened. It was determined that, in general, the wave environment (and thus the erosion potential) appeared to be greater during the short‐lived cold fronts than during times when no cold fronts were active. Key Points: Slow‐moving cold fronts lead to more energetic waves in confined bays and greater potential for salt marsh erosion Wetlands inundation caused by coincident cold front‐driven water levels and high tide weakens the impact of energetic waves on marsh edge Forcing spectral wave models with wind gusts, rather than averaged winds, leads to improved predictions of cold‐front driven surface waves when using default wave parameters in Simulating WAves Nearshore model